The Influence of Live Shopping on Consumer Purchase Decisions: Analysing the Role of Social Commerce in Indonesia’s Retail Sector - Irfan, Andi; Yadin S, Andi Nur; Hafipah, Hafipah; Adi, Yusram (The South East Asian Journal of Management, 2025)
Research Aims: This study examines the influence of live shopping on consumer purchase decisions in Indonesia, focusing on key features such as interactivity, promotional urgency, and influencer marketing. It also investigates the mediating effect of consumer trust and the moderating role of social commerce experience. Design/Methodology/Approach: A quantitative approach was employed, using survey data from 265 Indonesian consumers who engage in live shopping. The analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS. Research Findings: Interactivity, promotional urgency, and influencer marketing significantly impact consumer purchase decisions, both directly and indirectly through consumer trust. Promotional urgency exerts the strongest effect, emphasising the power of time-sensitive sales tactics. Social commerce experience moderates these relationships, with experienced consumers responding more strongly to live shopping strategies. Theoretical Contribution/Originality: This study expands the literature on social commerce by integrating live shopping elements into the S-O-R model and Trust Theory. It provides empirical evidence of how interactivity, urgency-driven promotions, and influencer credibility shape real-time purchase decisions. Managerial Implication in the South East Asian Context: Businesses in Southeast Asia should enhance live shopping by improving interactivity, leveraging urgency-based promotions, and strengthening influencer collaborations. Research Limitation & Implications: The study is limited to Indonesia, affecting its broader applicability. Its cross-sectional nature and self-reported data may introduce bias. Future research should explore regional differences, behavioural analytics, and longitudinal studies on evolving consumer behaviours in live shopping.